A subset of OPCs do not express Olig2 during development which can be increased in the adult by brain injuries and complex motor learning. Issue 2 (29th October 2022) - Fang, Li‐Pao; Liu, Qing; Meyer, Erika; Welle, Anna; Huang, Wenhui; Scheller, Anja; Kirchhoff, Frank; Bai, Xianshu
Abstract: Oligodendrocyte precursor cells (OPCs) are uniformly distributed in the mammalian brain; however, their function is rather heterogeneous in respect to their origin, location, receptor/channel expression and age. The basic helix–loop–helix transcription factor Olig2 is expressed in all OPCs as a pivotal determinant of their differentiation. Here, we identified a subset (2%–26%) of OPCs lacking Olig2 in various brain regions including cortex, corpus callosum, CA1 and dentate gyrus. These Olig2 negative (Olig2 neg ) OPCs were enriched in the juvenile brain and decreased subsequently with age, being rarely detectable in the adult brain. However, the loss of this population was not due to apoptosis or microglia‐dependent phagocytosis. Unlike Olig2 pos OPCs, these subset cells were rarely labeled for the mitotic marker Ki67. And, accordingly, BrdU was incorporated only by a three‐day long‐term labeling but not by a 2‐hour short pulse, suggesting these cells do not proliferate any more but were derived from proliferating OPCs. The Olig2 neg OPCs exhibited a less complex morphology than Olig2 pos ones. Olig2 neg OPCs preferentially remain in a precursor stage rather than differentiating into highly branched oligodendrocytes. Changing the adjacent brain environment, for example, by acute injuries or by complex motor learning tasks, stimulated the transition of Olig2 pos OPCs to Olig2 neg cells in the adult. Taken together, our results demonstrate that OPCs transiently suppress Olig2 upon changes of the brain activity. Main Points: A subset of OPCs do not express Olig2, of which population peaks in the juvenile brain while wanes with age. Plastic changes of the brain by acute injuries or complex motor learning stop the expression of Olig2 in OPCs.